Outcomes of Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Mesothelioma: Experience of a Peritoneal Surface Malignancy Center. Issue 12 (December 2015) - Aydin, Nail; Sardi, Armando; Milovanov, Vladimir; Nieroda, Carol; Sittig, Michelle; Nunez, Maria F.; Jimenez, William; Gushchin, Vadim
Diffuse malignant peritoneal mesothelioma (DMPM) is an uncommon malignancy, which can be difficult to treat. Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) have evolved as the treatment of choice when complete cytoreduction is to be achieved. This study reports the outcomes of CRS/HIPEC for peritoneal mesothelioma performed in a center for peritoneal surface malignancy. A retrospective analysis of a prospective database of 389 CRS/ HIPEC procedures identified 23 patients who underwent CRS/HIPEC for DMPM from 1999 to 2014. Gender, age at diagnosis, age at surgery, previous surgeries, follow-up time, peritoneal cancer index (PCI) score, completeness of cytoreduction (CC), pathology, and overall survival (OS) were analyzed. The univariate analysis was used to determine the prognostic value of age, gender, neoadjuvant chemotherapy, histopathology of the tumor, PCI, CC, and lymph node status on survival. Mean follow-up time from surgery was 31 months (range = 0.5–124). The median PCI score was 28, and 77 per cent had PCI ≥20. CC 0–1 was achieved in 65 per cent of cases. One- and 5-year actuarial OS rates from diagnosis were 86 per cent and 60 per cent, respectively. One- and 5-year actuarial OS from HIPEC was 70 per cent and 64 per cent, respectively. The univariate analysis showed that the CC was the only significant prognostic factor. Patients with DMPM may achieve long-term survival when treated with CRS/HIPEC. The CC is the most significant prognostic factor for long-term survival.